Influence of Residential Area Movement on the Performance of Kranggan Cibubur Road Section - Akbardin, Juang; Nurani, Intan Inti; Ma’soem, Dadang Mohamad (Universitas Ibn Khaldun Bogor, 2025)
The population of Bekasi and Depok City continues to increase, so the need for housing will also increase. To fulfill the need for housing, settlements will continue to develop. With the continued development of settlements, the volume of surrounding traffic will also increase. When the increase in traffic volume is not balanced with an increase in the capacity of the road section, there will be long queues of vehicles and long travel times. The purpose of this study is to determine the generation of movements generated from settlements. The results of this study are the estimation of movement generation from Kranggan Permai housing with a linear regression equation model, namely multiple Y1 = -0.007 + 0.011X1 + 0.649X4 + 0.118X5 + 0.336X7 with a generation value of 512.94 and Cibubur housing with a regression equation model, namely Y2 = 0.929 + 0.530X4 + 0.388X6 + 0.423X7 with a generation value of 603.043 smp/hour.